Structural study and vibrational assignments of anticonvulsant topiramate by using dft calculations and two harmonic force fields - Ruiz Hidalgo, José (2020)
B3LYP/6-311++G** calculations have been combined with the scaled quantum mechanical force field (SQMFF) methodology to study structural and vibrational properties of anticonvulsant topiramate (TPM) agent. The 123 vibration modes expected for TPM were completely assigned, considering two harmonic force fields. In one case, C2V symmetries were considered for both SO2 and NH2 groups, while in the other one C2V and C3V symmetries for the NH2 and SO3 groups, respectively. The calculated harmonic vibrational frequencies are consistent with the experimental IR and Raman spectra in the solid phase. Very good concordances were found between the theoretical structures in gas phase and aqueous solution and the corresponding experimental reported. Thus, the fused five-membered ring in TPM produces that the pyranose ring adopts distorted twist-boat conformation, as was experimentally observed. In solution, all calculations were performed with the self-consistent reaction force (SCRF) method by the integral equation formalism variant polarised continuum (IEFPCM) and universal solvation model density (SMD) models. The corrected solvation energy value for TPM in aqueous solution by total non-electrostatic terms and by ZPVE is-1066.10 kJ/mol. The bond orders have evidenced that the three O atoms are not linked of the same form to S atom. Hence, the S atom of TPM is practically tetra-coordinate in both media, as evidenced by the high negative MK and NPA charges on the O atoms linked to it. The AIM study supports the higher stability of TPM in the gas phase while the NBO calculations suggest higher stability in solution. Gap values support the higher reactivity of TPM in solution than in the gas phase. The scaled force constant for both cases are reported for the first time. Comparisons of predicted1H-and13C-NMR spectra with the corresponding experimental ones reveal very good concordances.